2021
DOI: 10.1302/2058-5241.6.200153
|View full text |Cite
|
Sign up to set email alerts
|

Treatment strategies for scapular spine fractures: a scoping review

Abstract: Fractures of the scapular spine are relatively rare and can occur without (1) or with (2) association to a reverse shoulder arthroplasty (RSA). To date there are only limited data on the topic. The aim of this scoping review was to identify all available literature and report current treatment concepts. A scoping review was conducted by searching PubMed for relevant studies between 2000 and October 2020. All studies were included which gave detailed descriptions of the treatment strategy. A total of 21 studies… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Cassidy 3 did not report the type of implant been used among their pooled data of SSF. Sußiek 17 reported pooled result of 11 studies reporting SSF after RSA; among the 50 cases, 2 did not report the type of implant, 21 used Grammont style RSA (mainly Delta III, Depuy Synthes, Raynham, MA, USA), and 27 lateralized implants (mainly Ascend flex; Tornier, Bloomington, MN, USA following by DJO surgical, Lewisville, TX, USA).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cassidy 3 did not report the type of implant been used among their pooled data of SSF. Sußiek 17 reported pooled result of 11 studies reporting SSF after RSA; among the 50 cases, 2 did not report the type of implant, 21 used Grammont style RSA (mainly Delta III, Depuy Synthes, Raynham, MA, USA), and 27 lateralized implants (mainly Ascend flex; Tornier, Bloomington, MN, USA following by DJO surgical, Lewisville, TX, USA).…”
Section: Discussionmentioning
confidence: 99%
“…In Sußiek 17 review, they identified 11 studies including 69 patients who had spine of scapular fracture with RSA. Nearly all of those 62 patients treated nonoperatively were limited with their shoulder function at the final follow-up and only 6 of them had bony union (although many did not have reported radiographic follow-up, so the number probably underrated).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these 11 patients, only two had multiple disruptions of the SSSC, which would have required early surgical treatment if the circumstances allowed [ 40 , 47 ]. As the potential complications of nonoperative management include painful fracture nonunion or increasing fragment displacement [ 40 , 86 88 ], periodic imaging observations are required during conservative treatment until the bone union is achieved. However, although displacement is the indication for surgery in patients with apophyseal fractures, most authors did not specify the degree of displacement [ 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…Operative treatment of the acromion has been described, most commonly involving open reduction and internal fixation of postoperative fractures. 4 However, achieving fixation is difficult in the setting of small fragments and is associated with the risk of complications, as well as the potential need for subsequent hardware removal. Thus, an alternate consideration for small fractures may be excision alone.…”
mentioning
confidence: 99%